RNA tape sampling in cutaneous lupus erythematosus discriminates affected from unaffected and healthy volunteer skin - Joseph F Merola; Nathalie Franchimont; Christopher Roberts; Alice Thai; Xueli Zhang; Wenting Wang; Carrie G Wager; Stefan Hamann; Cristina Musselli; Galina Marsh; Dania Rabah; Catherine Barbey; et al. (Lupus Science and Medicine)
Objective Punch biopsy, a standard diagnostic procedure for patients with cutaneous lupus erythematosus (CLE) carries an infection risk, is invasive, uncomfortable and potentially scarring, and impedes patient recruitment in clinical trials. Non-invasive tape sampling is an alternative that could enable serial evaluation of specific lesions. This cross-sectional pilot research study evaluated the use of a non-invasive adhesive tape device to collect messenger RNA (mRNA) from the skin surface of participants with CLE and healthy volunteers (HVs) and investigated its feasibility to detect biologically meaningful differences between samples collected from participants with CLE and samples from HVs.Methods Affected and unaffected skin tape samples and simultaneous punch biopsies were collected from 10 participants with CLE. Unaffected skin tape and punch biopsies were collected from 10 HVs. Paired samples were tested using quantitative PCR for a candidate immune gene panel and semi-quantitative immunohistochemistry for hallmark CLE proteins.Results mRNA collected using the tape device was of sufficient quality for amplification of 94 candidate immune genes. Among these, we found an interferon (IFN)-dominant gene cluster that differentiated CLE-affected from HV (23-fold change; p<0.001) and CLE-unaffected skin (sevenfold change; p=0.002), respectively. We found a CLE-associated gene cluster that differentiated CLE-affected from HV (fourfold change; p=0.005) and CLE-unaffected skin (fourfold change; p=0.012), respectively. Spearman’s correlation between per cent area myxovirus 1 protein immunoreactivity and IFN-dominant mRNA gene cluster expression was highly significant (dermis, rho=0.86, p<0.001). In total, skin tape-derived RNA expression comprising both IFN-dominant and CLE-associated gene clusters correlated with per cent area immunoreactivity of some hallmark CLE-associated proteins in punch biopsies from the same lesions.Conclusions A non-invasive tape RNA collection technique is a potential tool for repeated skin biomarker measures throughout a clinical trial.